Acute Displaced Fracture of Lateral Acromion after Reverse Shoulder Arthroplasty: A Case Report and Surgical Technique - Chul-Hyun Cho; Jae-Won Jung; Young-Jae Lim; Sang-Soo Na; Du-Han Kim (Clinics in Shoulder and Elbow, 2019)
Acromial fractures are well-documented complications subsequent to reverse shoulder arthroplasty (RSA), and most appear as stress fractures with no history of single trauma. To date, no study has reported the occurrence of acute displaced acromial fracture due to sudden strong deltoid contraction during heavy work. Displacement of the fracture results in a challenging surgery since it is difficult to obtain adequate fixation in thin and osteoporotic bones. We report a rare case of acute displaced acromial fracture after successful RSA treatment, using a novel technique of open reduction and internal fixation, applying two 4.5 mm cannulated screws and lateral clavicle pre-contoured plate.